Zhodnocení hospodaření obce Omice - Paterová, Michala (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Tato bakalářská práce se zabývá zhodnocením hospodaření obce Omice v letech 2006 – 2009. Cílem této práce je analyzovat příjmy a výdaje rozpočtu obce a zhodnotit hospodaření obce. První část je zaměřena na teoretické poznatky. Druhá část analyzuje a hodnotí příjmy a výdaje za poslední čtyři roky. Poslední část obsahuje návrhy na zlepšení hospodaření obce.

This bachelor´s thesis deals with the evaluation of the municipality management in Omice during years 2006 – 2009. The aim of this work is analyzes receipts and expenditures budget of the municipality and evaluates municipality of management. The first part of this thesis is focused on theoretical knowledge. The second part analyzes and evaluates receipts and expenditures in last four years. The last part includes the suggestions for improving of the economy of the municipality.
The Evaluation of the Municipality Management in Omice
Keywords: Obec; rozpočet; rozpočtová soustava; rozpočtová skladba; financování obce; příjmy; výdaje; Municipality; budget; budget system; budget structure; financing of the municipality; receipts; expenditures